Spatial Documentation of Traditional Coppersmithing Workshops in Patan, Nepal: A Comparative Study - Tamrakar, Lisama; Shrestha, Samriddhi; Shrestha, Sadichchha; Rana, Shreema (Journal of Himalaya College of Engineering, 2025)
This research documents traditional copper smithing practices in Patan, Nepal, focusing on the methods, techniques, and spatial requirements of this craft. Traditional metal crafting is an essential facet of Nepal’s cultural heritage, as exemplified by the ornate Hindu and Buddhist temples and intricate metalwork found in the country. The study emphasizes the repousse technique, which involves shaping thin sheets of metals such as copper, silver, and gold into intricate relief patterns using hammering and specialized techniques. Through comparative documentation of a residential-scale workshop and an industrial-scale facility in Patan, this research examines spatial arrangements, environmental conditions, and safety provisions. While general building codes and occupational health standards exist in Nepal, these do not provide specific guidelines for traditional craft workshops. The study explores the occupational challenges faced by craftsmen working in workshop spaces that have evolved organically within existing structures. This research has certain limitations as it focuses exclusively on coppersmiths workshops using the repousse technique, and concentrates on spatial requirements rather than broader socioeconomic and cultural factors. Nevertheless, this study establishes foundational spatial documentation that can inform future development of appropriate guidelines for traditional metal craft workshop design.